2021
DOI: 10.3390/jcm10245972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Withdrawal and Slow Taper of Antiseizure Medications during Video Electroencephalographic Monitoring: Efficacy for Shortening of Hospital Stay

Abstract: Antiepileptic medications (ASMs) are withdrawn at the epilepsy monitoring unit to facilitate seizure recordings. The effect of rapid tapering of ASMs on the length of hospital stay has not been well documented. We compared the mean length of hospital stay between patients who underwent acute ASM withdrawal and slow dose tapering during long-term video electroencephalography (EEG) monitoring. We retrospectively investigated 57 consecutive patients admitted to the epilepsy monitoring unit regarding the mean leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…All patients included in the study completed the LTM within 2–6 days, although 20 patients (26.7%) in the URW group and five patients (14.3%) in the RW group did not experience any seizures. The LTM duration for rapid taper and slow taper of medications was significantly different in prior studies, but did not reach significance in the present study ( p = 0.14) ( 16 , 19 ). The main reasons for the difference were the different taper protocols and limitation with regards to the LTM duration in our EMU.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…All patients included in the study completed the LTM within 2–6 days, although 20 patients (26.7%) in the URW group and five patients (14.3%) in the RW group did not experience any seizures. The LTM duration for rapid taper and slow taper of medications was significantly different in prior studies, but did not reach significance in the present study ( p = 0.14) ( 16 , 19 ). The main reasons for the difference were the different taper protocols and limitation with regards to the LTM duration in our EMU.…”
Section: Discussioncontrasting
confidence: 86%
“…However, there is little published literature on the subject, and a better evidence base is needed to inform ASM reduction decisions in the EMU. Several studies have reported ASM tapering regimens for LTM ( 4 , 7 , 16 ), with few cases comparing seizure rates and adverse effects of slower versus faster discontinuation ( 17–19 ). Most studies used observational designs, and changes in patient populations and medication regimens make it difficult to extrapolate the utility and safety of different discontinuation rates from these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation